Greco-Roman culture and the New Testament : studies commemorating the centennial of the Pontifical Biblical Institute - Aune, David E. (David Edward); Brenk, Frederick E.; Pontificio Istituto biblico (Leiden ; Boston : Brill, 2012)
Focusing on a strength of the faculty of the Pontifical Biblical Institute, this volume is a collection of nine essays by an international group of scholars who have used texts from the Greco-Roman world to illuminate various aspects of the New Testament.
Introduction / Frederick E. Brenk -- The role of rhetorical elaboration in the formation of Mark's Passion narrative (Mark 14:43-16:8) : an enquiry / Justin Taylor -- Logos and pneuma in the Fourth Gospel / Troels Engberg-Pedersen -- The enigma of imperial cultic activities and Paul in Corinth / Bruce W. Winter -- Pauline Paraenesis in Romans 12 and Greek gnomic wisdom / Dieter Zeller -- Most beautiful and divine : Graeco-Romans (especially Plutarch) and Paul, on love and marriage / Frederick E. Brenk -- Clement of Alexandria on woman and marriage in the light of the New Testament household codes / Gretchen J. Reydams-Schils -- Traveling up and away : journeys to the upper and outer regions of the world / Adela Yarbro Collins -- The polyvalent imagery of Rev 3:20 in the light of Greco-Egyptian divination texts / David E. Aune -- The Sibyl and the apocalypses : generic relationships in Hellenistic Judaism and early Christianity / John J. Collins.
Includes bibliographical references and indexes.
Master record variable field(s) change: 072
Keywords: Pontificio Istituto biblico; Bible. -- Criticism, interpretation, etc; Pontificio Istituto biblico; Bible; Christianity and culture -- History -- Early church, ca. 30-600.; Christian literature, Early -- History and criticism; Civilization, Greco-Roman.; RELIGION -- Biblical Criticism & Interpretation -- New Testament; Christian literature, Early; Christianity and culture -- Early church; Civilization, Greco-Roman.; 30-600; Electronic books; Criticism, interpretation, etc; History; Electronic book